ANALISIS GOVERNMENT PUBLIC RELATIONS KOMINFO SURABAYA MELALUI INSTAGRAM @SURABAYA - Putri Cendana (Universitas 17 Agustus 1945 Surabaya, 2026)
The development of digital technology has encouraged the government to utilize social media as a public communication medium in delivering information to society. One of the social media platforms used by the government is Instagram through the @surabaya account managed by Surabaya Communication and Informatics Office. This study aims to analyze the Government Public Relations activities of Surabaya Communication and Informatics Office through Instagram @surabaya in disseminating public information. This research uses the Government Public Relations theory proposed by Scott M. Cutlip which explains the role of government public relations in building public communication through digital media. The research method used is descriptive qualitative with data collection techniques through observation, documentation, and literature study. Data analysis uses the model of Matthew B. Miles and A. Michael Huberman consisting of data reduction, data presentation, and conclusion drawing. The results show that Instagram @surabaya is utilized as a Government Public Relations medium in delivering public information quickly, informatively, and interactively. Surabaya Communication and Informatics Office uses various visual contents such as photos, videos, reels, and captions to improve information dissemination to the public. In addition, Instagram is also used as a public communication medium between the government and society through digital interaction features. This study indicates that social media has an important role in supporting government public communication in the digital era. Keywords: Government Public Relations, Instagram, Surabaya Communication Office, Social Media.